Polyisocyanopeptide hydrogels: A novel thermo-responsive hydrogel supporting pre-vascularization and the development of organotypic structures. (1st April 2018) - Zimoch, Jakub; Padial, Joan Simó; Klar, Agnes S.; Vallmajo-Martin, Queralt; Meuli, Martin; Biedermann, Thomas; Wilson, Christopher J.; Rowan, Alan; Reichmann, Ernst
Graphical abstract: Abstract: Molecular and mechanical interactions with the 3D extracellular matrix are essential for cell functions such as survival, proliferation, migration, and differentiation. Thermo-responsive biomimetic polyisocyanopeptide (PIC) hydrogels are promising new candidates for 3D cell, tissue, and organ cultures. This is a synthetic, thermo-responsive and stress-stiffening material synthesized via polymerization of the corresponding monomers using a nickel perchlorate as a catalyst. It can be tailored to meet various demands of cells by modulating its stiffness and through the decoration of the polymer with short GRGDS peptides using copper free click chemistry. These peptides make the hydrogels biocompatible by mimicking the binding sites of certain integrins. This study focuses on the optimization of the PIC polymer properties for efficient cell, tissue and organ development. Screening for the optimal stiffness of the hydrogel and the ideal concentration of the GRGDS ligand conjugated with the polymer, enabled cell proliferation, migration and differentiation of various primary cell types of human origin. We demonstrate that fibroblasts, endothelial cells, adipose-derived stem cells and melanoma cells, do survive, thrive and differentiate in optimized PIC hydrogels. Importantly, these hydrogels support the spontaneous formation of complex structures like blood capillaries in vitro . Additionally, we utilized the thermo-responsive properties of the hydrogels for a rapid and gentle recovery of viable cells. Finally, we show that organotypic structures of human origin grown in PIC hydrogels can be successfully transplanted subcutaneously onto immune-compromised rats, on which they survive and integrate into the surrounding tissue. Statement of Significance: Molecular and mechanical interactions with the surrounding environment are essential for cell functions. Although 2D culture systems greatly contributed to our understanding of complex biological phenomena, they cannot substitute for crucial interaction that take place in 3D. 3D culture systems aim to overcome limitations of the 2D cultures and answer new questions about cell functions. Thermo-responsive biomimetic polyisocyanopeptide (PIC) hydrogels are promising new candidates for 3D cell, tissue, and organ cultures. They are synthetic and can be tailor to meet certain experimental demands. Additionally, they are characterized by strain-stiffening, a feature crucial for cell behaviour, but rare in hydrogels. Their thermos-responsive properties enable quick recovery of the cells by a simple procedure of lowering the temperature.